Satellite DNA and chromosomal evolution in Ctenomys rodents: a necessary clarification - Rossi, Maria Susana (2011)
Ctenomys is a quite large group of South American subterranean rodents (more than 60 species) that exhibits the widest range of karyotype diversity in mammals with chromosomal diploid numbers (2n) ranging from 10 to 70. Ctenomys has been considered as an example of explosive cladogenesis triggered by chromosomal repatterning [for a comprehensive classical review on Ctenomys , see Reig et al., 1990]. Chromosomal repatterning has been related to factors that reach from the population down to the genomic level. Recurrent contractions and expansions of repetitive Pvull Ctenomys sequence (RPCS), the major heterochromatic satellite DNA present in these genomes, have been related to chromosomal evolution in Ctenomys [Rossi et al., 1995; Slamovits et al., 2001].